pdx1 knockout leads to a diabetic nephropathy-like phenotype in zebrafish and identifies phosphatidylethanolamine as metabolite promoting early diabetic kidney damage - Wiggenhauser, Lucas; Metzger, Lena; Bennewitz, Katrin; Soleymani Zaraj Abadi, Silas; Boger, Mike; Tabler, Christoph Tobias; Haußer-Siller, Ingrid; Sticht, Carsten; Wohlfart, Paulus; Volk, Nadine; Heidenreich, Elena; Büttner, Michael; et al. (Diabetes, 2022)
The pdx1−/− zebrafish mutant was recently established as a novel animal model of diabetic retinopathy. In this study, we investigate whether knockout of pdx1 also leads to diabetic kidney disease (DKD). pdx1−/− larvae exhibit several signs of early DKD, such as glomerular hypertrophy, impairments in the filtration barrier corresponding to microalbuminuria, and glomerular basement membrane (GBM) thickening. Adult pdx1−/− mutants show progressive GBM thickening in comparison with the larval state. Heterozygous pdx1 knockout also leads to glomerular hypertrophy as initial establishment of DKD similar to the pdx1−/− larvae. RNA sequencing of adult pdx1+/− kidneys uncovered regulations in multiple expected diabetic pathways related to podocyte disruption and hinting at early vascular dysregulation without obvious morphological alterations. Metabolome analysis and pharmacological intervention experiments revealed the contribution of phosphatidylethanolamine in the early establishment of kidney damage. In conclusion, this study identified the pdx1 mutant as a novel model for the study of DKD, showing signs of the early disease progression already in the larval stage and several selective features of later DKD in adult mutants.